Religion Identity And Political Polarization: How Does Labeling Make It Worst? - Hayat, Nahrul; Nurhakki, Nurhakki (LP2M IAIN Palopo, 2022)
Prabowo's joining of President Jokowi's cabinet is expected to end the polarization of tadpoles versus